PERBEDAAN HUKUM PEMBUKTIAN DALAM PERSPEKTIF HUKUM ACARA PIDANA DAN PERDATA - Hendri Jayadi Pandiangan (to-ra, 2017)
Abstract Proof is the act of proving that in general it has the same purpose, namely to provide certainty about the truth of an event. The act of proving in a trial is indeed used the notion of juridical proof, that is, proof in the court is not possible for logical and absolute proof, therefore in examining the evidence in the trial it is known as things that are close to the truth. But actually if it is analyzed more deeply in certain matters it can also happen that the evidence in the trial is logical and absolute. Proof in the practical order is a very important thing to test the truth or legal facts that actually occur. The Defendantâ€™s fate in the trial at the Court was very much determined by the evidence that could be used as the basis for the judge in making a verdict against him. In such civil procedure, the fate of the parties, both the Plaintiff and the Defendant, is very much determined by the presentation of the evidence by the parties. The evidentiary difference in criminal procedure law and civil procedural law is that in the criminal proof the proof of system is â€œnegatief wettelijk stelselâ€, the system of verification according to the law negatively is a theory of a combination of a positive legal proof system with conviction-in time. Whereas the characteristic of civil proof is â€œaudi et alterem partemâ€, the party who postulates that it must prove the argument. Keywords: hukum pembuktian, hukum acara pidana, hukum acara perdata